Arabic Phonological Competence and the Understanding of Islamic Legal Terminology in the Contemporary Era - Akla; Ahmad Arifin; Nur Hanifansyah; Mamluatur Rahmah; Khaled Hassan Al-Jabali (Faculty of Sharia, UIN Jurai Siwo Lampung, 2026)
The mastery of Arabic phonology (Ashwāt al-‘Arabiyyah) plays a fundamental role in the accurate interpretation of classical Islamic texts, yet its contribution to the understanding of Islamic legal terminology remains underexplored in contemporary Islamic education. This study investigates the relationship between Arabic phonological competence and students' understanding of Islamic legal terminology in the contemporary era, particularly within the context of Salafi Islamic boarding schools (pesantren) that rely heavily on kitab kuning as their primary learning resource. The research aims to assess students' levels of phonological competence, measure their mastery of Islamic legal terminology, and examine the extent to which phonological competence influences legal understanding. Employing a mixed-methods explanatory sequential design, the study collected quantitative data from 120 students via standardised tests measuring Arabic phonological competence and comprehension of Islamic legal terminology. The quantitative phase was followed by qualitative inquiry involving classroom observations, in-depth interviews, and document analysis to explain and contextualise the statistical findings. Quantitative data were analysed using correlation and regression analyses, and qualitative data were analysed using thematic analysis. The findings demonstrate a statistically significant positive relationship between Arabic phonological competence and the understanding of Islamic legal terminology. Students with higher levels of phonological mastery exhibited greater accuracy in identifying, interpreting, and applying legal concepts embedded in classical fiqh texts. Qualitative evidence further reveals that phonological awareness facilitates semantic processing, improves retention of legal concepts, and strengthens comprehension of qawāʿid fiqhiyyah through recurring sound patterns that function as cognitive anchors. Conversely, inadequate phonological competence frequently led to pronunciation errors, lexical confusion, and misinterpretation of legal meanings. This study contributes to the growing scholarship on Arabic language pedagogy and Islamic legal education by demonstrating that phonological competence is not merely a linguistic skill but also a crucial cognitive foundation for legal literacy. The findings underscore the need to integrate systematic phonological instruction into contemporary kitab kuning learning to enhance students' legal comprehension and interpretive accuracy.